2013
DOI: 10.1111/jne.12038
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxytocin and Vasopressin do not Predict Neuropeptide Concentrations in Human Cerebrospinal Fluid

Abstract: The involvement of the neuropeptides oxytocin (OXT) and vasopressin (AVP) in human socio-emotional behaviours is attracting increasing attention. There is ample evidence for elevated plasma levels upon a wide variety of social and emotional stimuli and scenarios, ranging from romantic love via marital distress up to psychopathology, with cause versus consequence being largely unclear. The present study examined whether plasma levels of both OXT and AVP are reflective of central neuropeptide levels, as assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 54 publications
7
141
3
Order By: Relevance
“…It remains unclear whether peripheral OXT or AVP levels represent the central neuropeptide levels and activities. Some studies in pregnant women [51], adult suicide attempters [52], and adult patients undergoing surgical procedures [53] have indicated a lack of correlation between OXT concentrations in plasma and cerebrospinal fluid (CSF). However, a recent study on children and adult patients have reported a positive correlation of OXT levels between the two compartments and this relationship is stronger when only children are included in the analysis [54].…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether peripheral OXT or AVP levels represent the central neuropeptide levels and activities. Some studies in pregnant women [51], adult suicide attempters [52], and adult patients undergoing surgical procedures [53] have indicated a lack of correlation between OXT concentrations in plasma and cerebrospinal fluid (CSF). However, a recent study on children and adult patients have reported a positive correlation of OXT levels between the two compartments and this relationship is stronger when only children are included in the analysis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly some studies have shown differential central and peripheral release of the peptides under certain conditions, in humans (Kagerbauer et al, 2013) and in rodents (Wotjak et al, 1998). On the other hand, several studies have shown a relation between peripheral concentration levels and behaviors controlled centrally (Fries et al, 2005;Strathearn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most human studies rely on plasma OT concentrations for the prediction of behavioral phenotypes, assuming that these peripherally derived measures reflect central OT concentrations. This basic premise has been challenged by studies showing that there is no correlation between plasma and CSF OT concentrations (Altemus et al, 2004; Kagerbauer et al, 2013), but confirmed by others, which found significant between-compartment correlations (Carson et al, 2015). Divergent findings like these, whose clarification is pivotal for advancement of behavioral and psychiatric neuroendocrinology, may partly result from methodological heterogeneity, which leads to an issue of particular concern.…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%